Therapeutic Response of CCKBR-Positive Tumors to Combinatory Treatment with Everolimus and the Radiolabeled Minigastrin Analogue [177Lu]Lu-PP-F11N - Michal Grzmil; Stefan Imobersteg; Alain Blanc; Stephan Frank; Roger Schibli; Martin P. Béhé (MDPI AG, 2021)
The inhibition of the mammalian target of rapamycin complex 1 (mTORC1) by everolimus (RAD001) was recently shown to enhance the tumor uptake of radiolabeled minigastrin. In this paper, we investigate if this finding can improve the in vivo therapeutic response to [177Lu]Lu-PP-F11N treatment. The N-terminal DOTA-conjugated gastrin analogue PP-F11N (DOTA-(DGlu)6-Ala-Tyr-Gly-Trp-Nle-Asp-Phe) was used to evaluate treatment efficacy in the human A431/CCKBR xenograft nude mouse model in combination with RAD001. Both RAD001 and [177Lu]Lu-PP-F11N single treatments as well as their combination inhibited tumor growth and increased survival. In concomitantly treated mice, the average tumor size and median survival time were significantly reduced and extended, respectively, as compared to the monotherapies. The histological analysis of kidney and stomach dissected after treatment with RAD001 and [177Lu]Lu-PP-F11N did not indicate significant adverse effects. In conclusion, our study data demonstrate the potential of mTORC1 inhibition to substantially improve the therapeutic efficacy of radiolabeled minigastrin analogues in CCKBR-positive cancers.